The Adaptation of Learning Models and Instructional Methods in Islamic Education at Madrasah Ibtidaiyah in Responding to the Challenges of Generation Alpha - Muhammad Ihsan; Rabiatul Ismi; Nur Aisyah; Imar Imar; Tamara Anggina Putri; Maulana Fathur Rizqia; Ali Iskandar Zulkarnain (The Future of Education Journal, 2026)
This study examines the adaptation of learning models and teaching methods in Islamic Religious Education (PAI) at Madrasah Ibtidaiyah (MI) in responding to the learning characteristics of the alpha generation. The research employed a library research approach by analyzing data obtained from books, academic journals, Problem Based Learning (PBL), Contextual Teaching and Learning (CTL), and Project Based Learning (PjBL) can support more interactive, meaningful, and student-centered learning processes in PAI instruction. Furthermore, teaching methods including lectures, discussions, question-and-answer sessions, demonstrations, and storytelling remain important when applied flexibly according to students learning needs. The appropriate adaptation of learning model and methodes is considered capable of strengthening students understanding of Islamic teaching while also supporting the development of Islamic values and character.